Healthcare workers' attitudes to and compliance with infection control guidelines in the operating department at the university hospital of the West Indies, Jamaica - McGaw, Clarence David; Tennant, Ingrid; Harding, Hyacinth E; Cawich, Shamir O; Crandon, Ivor W; Walters, CA (International Journal of Infection Control, 2012)
Surgical operations provide opportunities for the transmission of infection between patients and healthcare workers (HCWs) and between patients. This risk may be increased in under-developed and developing countries by low compliance with infection control (IC) policies and precautions. This study investigated the attitude and compliance of HCWs in the operating department (OD) of a Jamaican teaching hospital, with the objective of obtaining data to design evidence-based interventions. A single-center, cross-sectional, descriptive study, using a self-administered questionnaire, was conducted between March-May, 2009. Ninety doctors and forty-two nurses, representing 73% and 75%, respectively, of their total OD population participated in the study. Reported compliance was low: only 17% of all participants were compliant with all of the seven infection control policies inquired into. The results also showed that HCWs were selective in what practices they adhered to: reported rates of compliance were high for hand-washing (100%), use of gloves (98%), use of gowns (83%) and facemasks (87%); but low for use of eye protection mask (56%), not re-sheathing needles (46%) and changing clothes when exiting and re-entering the OD (55%). Discrepancies were observed between attitude and compliance rates in such cases as ‘use of facemasks’- low favorable-attitude (68%) but high compliance; ‘use of eye protection masks’- high favorable-attitude (100%) but low compliance; and ‘not re-sheathing needles’- high favorable attitude (86%) but low compliance. Overall, nurses had higher favorable attitude (p<0.001) and compliance rates (p=0.008).than physicians. To improve HCWs adherence to guidelines, interventions must take account of those factors which determine human behaviour.